Don’t Let Your Thoughts Die - Shrestha, Bikash (Medical Journal of Shree Birendra Hospital, 2016)
They say that the diagnosis of end of life is by the diagnosis of brain death. And of course, as long as the brain is not dead, we do continue our thoughts. Sometimes, our thoughts are really powerful. These thoughts are meaningless unless we let others know about it. The best way to let our thoughts be known to others is to document it. There goes the importance of publishing our thoughts. And perhaps, this is the most consolidate manner of making ourselves immortal. Recently, during my fellowship in neonatology days in Delhi, I was literature searching for high frequency ventilation in neonates. During this adventure, I reached the website of “The American Journal of Physiology”, the official publication of The American Physiology Society. During this, I was mesmerized by their first publication which was dated January 1898!!! It was really worth noting that this society was established in 1887 and their publication started in 1898! Of course, the New England Journal of Medicine and the Lancet are one of the oldest publication journals dated 1812 and 1823 respectively but it was amazing that the branch of physiology had journals more than a century ago! Yes of course, no doubt, we may be lagging behind our thoughts for even more than a century. This has no limitation for us to catch up and head towards the future. It is never too late, unless we do not start it. Let’s go ahead and move along with time, sharing our thoughts and trying to keep ourselves and our institution immortal forever. All the best.